An investigation of the effect of toughness and brittleness indexes on ampere consumption and wear rate of a circular diamond saw (Rudarsko-geološko-naftni zbornik, 2018)
The circular diamond saw (CDS) is one of the major sawing machines in dimension stone processing plants. Predicting the performance of a circular diamond saw is very important to estimate the cost and the planning of the stone process- ing plants. The performance of a CDS depends on some important factors such as machine and tool characteristics, physical and mechanical characteristics of rock and tool wear rate. In this research, it is aimed to investigate the relation- ship between ampere consumption, brittleness indexes and toughness with the wear rate of a CDS. This aim was pursued by using a fully instrumented cutting rig to cut 14 types of hard rock at constant feed rates, cut depths and peripheral speeds. Wear rate, toughness and brittleness indexes were evaluated using simple and multiple curvilinear regression analysis and predicted models were developed. The results indicated that there is a significant correlation between wear rate, ampere consumption and toughness. It is concluded that, the wear rate of a CDS can be reliably estimated using a multiple curvilinear model which includes ampere consumption and toughness.